Understanding mass communication : a liberal arts perspective - DeFleur, Melvin L. (Melvin Lawrence), 1923-; Dennis, Everette E. (Boston : Houghton Mifflin, 1998)
Print media. Audio, visual, multimedia. Media industries and audiences. Media influences and issues.
Keywords: Mass media; Mass media